2011
DOI: 10.1007/s00167-011-1507-z
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic treatment of lateral epicondylitis: comparison of the outcome of ECRB release with and without decortication

Abstract: Arthroscopic release of the ECRB is an effective method of treatment in patients with recalcitrant lateral epicondylitis. Decortication of the lateral epicondyle leads to increased pain postoperatively and did not improve clinical results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 23 publications
(27 reference statements)
0
17
0
Order By: Relevance
“…4,5,8,14,19,20,24,[26][27][28] Multiple open, arthroscopic, and percutaneous surgical procedures have been described to treat elbow tendinopathy, all sharing the fundamental goals of removing the pathologic tendinotic tissue and stimulating a healing response. 5,6,10,20,22,25 These procedures have been effective in 75% to 90% of patients but expose patients to operative risks and a recovery that is often prolonged. 5,6,10,20,22,24,25 Sonographically guided percutaneous tenotomy using ultrasonic energy to remove diseased tissue has recently become available with the release of the TX1 device (Tenex Health Inc, Lake Forest, CA, USA).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4,5,8,14,19,20,24,[26][27][28] Multiple open, arthroscopic, and percutaneous surgical procedures have been described to treat elbow tendinopathy, all sharing the fundamental goals of removing the pathologic tendinotic tissue and stimulating a healing response. 5,6,10,20,22,25 These procedures have been effective in 75% to 90% of patients but expose patients to operative risks and a recovery that is often prolonged. 5,6,10,20,22,24,25 Sonographically guided percutaneous tenotomy using ultrasonic energy to remove diseased tissue has recently become available with the release of the TX1 device (Tenex Health Inc, Lake Forest, CA, USA).…”
mentioning
confidence: 99%
“…5,6,10,20,22,25 These procedures have been effective in 75% to 90% of patients but expose patients to operative risks and a recovery that is often prolonged. 5,6,10,20,22,24,25 Sonographically guided percutaneous tenotomy using ultrasonic energy to remove diseased tissue has recently become available with the release of the TX1 device (Tenex Health Inc, Lake Forest, CA, USA). 2,16,18 The U.S. Food and Drug Administration-approved TX1 procedure uses standard ultrasound guidance to place a proprietary needlelike device into the pathologic tendon region.…”
mentioning
confidence: 99%
“…As a result, during our study, we did not include the decortication procedure, unlike the original technique with decortication proposed by Baker et al [2]. They also reported they no longer perform decortication [1] and other authors [16] also concluded that decortication was not necessary because patients undergoing decortication experienced long-lasting pain relief. Our study suggests refractory lateral epicondylitis can be treated appropriately by the Baker technique without decortication.…”
Section: Discussionmentioning
confidence: 94%
“…Arthroscopic debridement also carries a small risk of nerve damage and elbow instability. Overall, these risks are less than 1% 3,10,11,25,27 .…”
Section: Complicationsmentioning
confidence: 96%